Faktor-Faktor yang Mempengaruhi Collaborative Governance dalam Penanganan Pekerja Migran Bermasalah di Kota Tanjungpinang - Sepriandi, Sigit; Hussein, Rahmawati (Universitas Medan Area, 2019)
Tanjungpinang is one of the areas that became the entry point for the shelter and repatriation of Deprived Migrant Workers (PMB) deported from Malaysia. The high number of PMBs deported from Malaysia through Tanjungpinang City, made the Tanjungpinang City Government overwhelmed in overcoming these problems. Therefore, to overcome this, the Tanjungpinang City Government collaborated and coordinated with various stakeholders to be able to resolve the situation. This study aims to analyze what factors influence collaborative governance by regional governments in handling PMB in Tanjungpinang. The method used is a qualitative method with a descriptive approach, data collection techniques using interview techniques, observation and documentation relating to handling PMB. Meanwhile data processing uses reduction techniques. The results of the study found that the factors that influence collaborative governance in handling PMB in Tanjungpinang City can be seen from the factors of social, cultural and government interests. From the analysis of these three factors, the factors of social and cultural structure do not significantly influence the course of collaboration. However, the government interest factor is a factor that causes the failure of a collaboration, including in terms of active participation from stakeholders in decision making.